EVALUASI SISTEM AGROFORESTRI SENGON DENGAN PADI GOGO TERHADAP SERANGAN CENDAWAN Rhizoctonia sp. Evaluation of Agroforestry System between Sengon with Upland Rice to Invection of Rhizoctonia sp. - Nofika Senjaya; Nurheni Wijayanto; Desta Wirnas; Achmad . (Jurnal Silvikultur Tropika, 2018)
Sengon is a fast growing species that popular to be cultivated in Indonesia. It can be planted in agroforestry system with agricultural crop such as upland rice (padi gogo). Agroforestry system between sengon and upland rice is vulnerable to fungi attack. Micro fungi that may attack upland rice and young sengon is Rhizoctonia sp. This research aimed to analyze the interaction of plants in agroforestry between sengon and upland rice as well as Rhizoctonia sp. attack. The experiment was performed in community forest in Cikarawang village which dominated by 2 years old sengon. Agroforestry system in cikarawang village affected significantly to harvest productivity of upland rice but not affected to growth of sengon. Statistical test performed also showed that Rhizoctonia sp. attack to upland rice did not affect the harvesting result, but only affected to plant morphology.Keywords: dimension, fungi, rice, productivity